2014
DOI: 10.3171/2014.4.peds13244
|View full text |Cite
|
Sign up to set email alerts
|

Differences in vascular endothelial growth factor receptor expression and correlation with the degree of enhancement in medulloblastoma

Abstract: Object Vascular endothelial growth factor (VEGF) is the major proangiogenic factor in many solid tumors. Vascular endothelial growth factor receptor (VEGFR) is expressed in abundance in pediatric patients with medulloblastoma and is associated with tumor metastasis, poor prognosis, and proliferation. Gadolinium enhancement on MRI has been suggested to have prognostic significance for some tumors. The association of VEGF/VEGFR and Gd enhancement in medulloblastoma has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Nevertheless, it is important to underline that our survival analyses were performed within the biologically relevant group of non-WNT/SHH tumours since WNT and SHH tumours have distinctive characteristics and should be analysed separately as independent cohorts. Very recent results published by Hervey-Jumper et al [ 19 ] indicated that the presence of enhancement did not correlate with worse patient prognosis, but the results were not related to biological subtypes. It was noticed in our work that majority of SHH tumours were extensively enhancing but patients are long term survivors.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, it is important to underline that our survival analyses were performed within the biologically relevant group of non-WNT/SHH tumours since WNT and SHH tumours have distinctive characteristics and should be analysed separately as independent cohorts. Very recent results published by Hervey-Jumper et al [ 19 ] indicated that the presence of enhancement did not correlate with worse patient prognosis, but the results were not related to biological subtypes. It was noticed in our work that majority of SHH tumours were extensively enhancing but patients are long term survivors.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the establishment of MRI protocols for longitudinal imaging over extended periods of time is crucial for dynamic qualitative and quantitative analysis of tumor progression, which should provide a better stratification of experimental cohorts based on tumor phenotype and behavior. Previous studies have used conventional MRI techniques for morphologic brain tumor imaging in mouse MB models, but similar to most human studies [36] , [37] , [38] , [39] , mouse MB MRI reports have largely focused on detection and monitoring of tumor burden at relatively advanced tumor stages. For example, T2-weighted (T2w) MRI has been used to define the location and extent of advanced MBs in mouse models [40] , [41] , [42] , while gadolinium-enhanced T1-weighted (T1w) imaging has been used to evaluate breakdown of the blood-brain barrier (BBB) and leakage of the contrast agent into MB tumors [40] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that VEGF-A can act directly on some tumor cell types in an autocrine manner to promote tumor growth and invasion [ 20 , 21 ]. A number of studies reveal the elevated levels of VEGF-A and VEGFR2 in medulloblastoma of human patients [ 45 , 46 ]. Recent studies also show that medulloblastoma cells express both VEGF-A and VEGFR2 [ 22 , 47 ].…”
Section: Discussionmentioning
confidence: 99%